In ovo yolk carotenoid and testosterone levels interactively influence female transfer of yolk antioxidants to her eggs - Giraudeau, Mathieu (Biol Lett, 2018)
Mothers can influence prenatal conditions by varying the amount of nutrients, hormones or antioxidants they provide to their developing young. Some of these substances even affect the transfer of these compounds in the next generation, but it is less clear how different maternally transmitted compounds interact with each other to shape reproductive resource allocation in their offspring. Here, we found that female Japanese quails (Coturnix japonica) that were exposed to high carotenoid levels during embryonic development transferred lower concentrations of yolk antioxidants to their own eggs later in life. This effect disappeared when both testosterone and carotenoid concentrations were manipulated simultaneously, showing long-term and interactive effects of these maternally derived egg components on a female's own egg composition. Given that exposure to high levels of testosterone during embryo development stimulates the production of reactive oxygen species (ROS) and impairs antioxidant defenses, we propose that carotenoids act as in ovo antioxidants in an oxidatively stressful environment (i.e. when levels of testosterone are high) but might have prooxidant properties in an environment where they are not used to counteract an increased production of ROS. In line with this hypothesis, we previously showed that prenatal exposure to increased concentrations of yolk carotenoids leads to a rise of oxidative damage at adulthood, but only when yolk testosterone concentrations were not experimentally increased as well. As a consequence, antioxidants in the body may be used to limit oxidative damage in females exposed to high levels of carotenoids during development (but not in females exposed to increased levels of both carotenoids and testosterone), resulting in lower amounts of antioxidants being available for deposition into eggs. Since prenatal antioxidant exposure is known to influence fitness-related traits, the effect detected in this study might have transgenerational consequences.